Harry Potter and the chamber of secrets - Rowling, J. K. (New York : Scholastic Inc, 1999)
When the Chamber is open again at the Hogwarts school for witchcraft and wizardy, second year student Harry Potter finds himself in danger from a dark power that has once more released on the school.
Keywords: Wizards -- fiction; Magic -- fiction